Femoral Fracture During Cesarean Section: A Case of Professional Liability? Case Presentation and Review of the Literature - Papi, Luigi; Gori, Federica; Turco, Sara; Perutelli, Alessandra (Archives of Clinical and Medical Case Reports, 2019)
Breech foetuses are commonly delivered via caesarean section to prevent trauma and decrease the risk of head entrapment, though extraction by abdominal route can very rarely lead to traumatic femur fracture. Typical site of fracture is femoral diaphysis. Although femur fracture is a relatively rare complication, it represents one of the most common fractures of the lower extremity presenting in newborns. A 3900 g female child born at 39 weeks of gestation by caesarean section, presented swelling and tenderness of the left lower extremity in the second day of life. There was no apparent bone disorder predisposing to femur fracture. Fracture of left diaphysis was successfully treated by immobilization with Pavlik harness, healing in a good position for 23 days. Three months after birth, radiogram revealed regular bone consolidation and fracture fully welded. One year after birth, both lower limbs showed a proper mobility with no dysmetria. Caesarean delivery reduces increasingly traumatic complications, especially in breech delivery compared with vaginal delivery, but does not eliminate possible accidental injuries of the newborn. Predisposing factors are many, especially breech presentation and foetuses with malpresentation. Clinicians must be aware that abdominal delivery does not preclude the occurrence of femur fractures.